PENGARUH TEKNOLOGI INFORMASI, KOMPETENSI, DAN MOTIVASI TERHADAP KINERJA PENYULUH DI KABUPATEN KARAWANG - Yuliasaputri, Syahnaz (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the influence of information technology mastery, competence, and work motivation on the performance of agricultural extension workers in Karawang Regency. The increasing demand for professionalism and the integration of digital technology in the agricultural sector position extension workers as strategic actors in supporting regional agricultural productivity and innovation. This research employed a quantitative approach using a survey method. The sample consisted of 128 respondents, determined using the Slovin formula from a population of 177 agricultural extension workers. Data were collected through questionnaires using a Likert scale and analyzed using validity and reliability tests, along with classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. Multiple linear regression analysis was applied to examine both partial and simultaneous effects among variables. The results indicate that information technology mastery, competence, and work motivation each have a positive and significant effect on the performance of agricultural extension workers. Simultaneously, these three independent variables explain 85.9% of the variance in extension workers’ performance, while the remaining percentage is influenced by other factors. These findings emphasize the importance of strengthening technological utilization, enhancing professional competence, and providing sustained motivational support to improve the performance of agricultural extension workers.